The Hummingbird Project year 2: decreasing distress and fostering flourishing in a pragmatic pre–post study - Platt, Ian Andrew; Hochard, Kevin D.; Tytherleigh, Michelle; Kannangara, Chathurika; Carson, Jerome; McFaul, Claudine; North, Catherine (Frontiers in Psychology, 2024)
Multi-component Positive Psychology Interventions (mPPIs) in secondary schools have been shown to improve mental health outcomes for young people. The Hummingbird Project mPPI is a six-week program of workshops designed to introduce a variety of positive psychology (PP) concepts to secondary school-aged children in schools to improve well-being, resilience, and hope. The effects on mental distress, however, were not explored. The current study, therefore, was designed to replicate the effects of the Hummingbird Project mPPI on positive mental health and to also explore the effects on symptoms of mental distress. Secondary school-aged children (N = 614; mean age = 11.46 years) from a sample of secondary schools located across the North West of England (N = 7) participated in the study; the majority of children were in Year 7 (94%). The PP concepts explored included happiness, hope, resilience, mindfulness, character strengths, growth mindset, and gratitude. The results showed significant improvements associated with the mPPI in well-being (as measured by the World Health Organization Well-Being Index; WHO-5), hope (as measured by the Children’s Hope Scale; CHS), and symptoms of mental distress (as measured by the Young Person’s Clinical Outcomes in Routine Evaluation; YP-CORE) from pre- to post-intervention. While acknowledging the limits due to pragmatic concerns regarding the implementation of a control group, the effectiveness of the Hummingbird Project mPPI on well-being was replicated alongside reducing the symptoms of mental distress. Future evaluation, however, will need to implement more robust designs and consider follow-up duration to assess the longer-term effects of the Hummingbird Project mPPI.